Values influencing the practice of investigative journalism in Malaysia : media practitioners’ perspectives - Adibah Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Investigative journalism has been an American phenomenon, heavily embedded with their values. Scholars mentioned individualism and press freedom as two founding values of investigative journalism practice in the West. This study attempts to explore values influencing the practice of investigative journalism from a different viewpoint, by investigating Malaysia as a democratic country, but having a controlled media environment. Malaysia is also an interesting research subject because it is a developing country with strong Eastern values. Using local yardsticks, this study explores values influencing the practice of investigative journalism in Malaysia from local media practitioners’ perspectives. This research aims to explore more than just the differences between Western and Eastern culture, but also to understand how those different values influence the practice. In-depth interviews were used to explore the perspectives of 16 media practitioners from various backgrounds including editors and journalists who work in mainstream and alternative media in Malaysia. Vast data generated from the interviews pointing to a different viewpoint from current literature. The data, which was thematically analysed, revealed interesting findings which differentiate between Malaysian and Western practices of investigative journalism. The Eastern perspective was found to be dominant, especially in terms of collectivism culture, value of press freedom, and religious teachings influence. This study also highlighted the importance of considering the cultural factor in evaluating any journalism practice in the world. The study concludes that local values and culture must be included as research elements to understand a country’s journalism practice.